"التعلم التنظيمي ودوره في تعزيز الابداع في المؤسسة العمومية - دراسة حالة جامعة الشهيد حمه لخضر-الوادي- " - دلال, بن قلية; سمية, زان; دليلة, رواص; بالباقي, خرفية (University of eloued جامعة الوادي, 2022)
"تهدف دراستنا إلى إظهار الدور الذي يلعبه التعلم التنظيمي في تعزيز الابداع في المؤسسة الاقتصادية، حيث يرتبط التعلم التنظيمي بالأنشطة الإدارية المتكررة بأنه عملية تصحيح الأخطاء وحل المشكلات عن طريق تغيير السياسات والسياقات المعيارية، والابداع التنظيمي هو مختلف الافكار والاساليب الجديدة والمطورة التي تعتمد عليها المنظمة للوصول الى تحقيق اهدافها وحاولنا الاجابة على الاشكالية المطروحة تم الاعتماد في الدراسة على اتبع المنهج الوصفي التحليلي، في الدراسة النظرية وذلك من خلال اتباع المنهج المسحي ووفي الجانب التطبيقي على الاستبيان، والذي وزع على 45 موظف وتم استرجاع 40 استبيان وكلها قابلة للدراسة والتحليل باستخدام أدوات إحصائية spss. وقد خلصت الدراسة إلى جملة من النتائج والتي تمثلت في كون التعلم التنظيمي يساهم في تعزيز الابداع في المؤسسة، كما انها توجد علاقة بين التعلم التنظيمي والابداع في المؤسسة، بحيث يعد الاهتمام بترقية قدرات المورد البشري الابداعية عاملا مهم في تحقيق احسن الخدمات، واتضح ان مؤسسة التعليم العالي والبحث العلمي جامعة الوادي الشهيد حمه لخضر تهتم بالتعلم التنظيمي والابداع التنظيمي لدى العاملين وتحقيق رضاهم وذلك بتقديم المؤسسة لخدمات تطابق مع توقعاتهم أو تفوقها. "" Our study aims to show the role that organizational learning plays in promoting creativity in the economic institution، where organizational learning is linked to repeated administrative activities as a process of correcting errors and solving problems by changing policies and normative contexts And organizational creativity is the various new and developed ideas and methods that the organization relies on to reach its goals And we tried to answer the problem at hand. The study relied on following the descriptive-analytical approach، in the theoretical study، by following the survey method، and in the practical aspect of the questionnaire، which was distributed to 45 employees and 40 questionnaires were retrieved، all of which can be studied and analyzed using spss statistical tools. Creativity in the organization.. The organizational contributes to enhancing creativity in the institution، and there is also a relationship between organizational learning and creativity in the institution، so that the interest in upgrading the creative capabilities of the human resource is an important factor in achieving the best services، and it turns out that the Institution of Higher Education and Scientific Research، University of the Martyr Valley Hama Lakhdar is interested in organizational learning And organizational creativity among employees and achieving their satisfaction by providing the institution with services that match or exceed their expectations "
ماستر ادارة اعمال
Keywords: التعلم التنظيمي، الابداع التنظيمي، الابداع; organizational learning، organizational creativity، creativity